Penerapan Manajemen Strategik Pendidikan Dalam Meningkatkan Profesionalitas Guru di Madrasah Ibtidaiyah Miftahul Ulum Peganden - Lailah Maulidiyah; Moh. Syafi’i (Departement of Mathematics Education, 2023)
One strategy to improve the quality of education is the implementation of strategic management. Which reason fundamental is that the concept of strategic management offers to schools to provide better and more adequate education for students. Achieving compatibility between environments school and strategic, school structure and processes, have a positive effect on teacher performance. education crisis faced by the Indonesian nation revolves around crisis management, in which education management is mobilization of all educational resources to achieve the set educational goals. Research methods used is descriptive qualitative research conducted at Madrasah Ibtidaiyah Miftahul Ulum Peganden. It is called qualitative research, because the main data source for this research is in the form of the words and the actions of the people observed or interviewed. Based on the results of the research, it gives a conclusion that Madrasah Ibtidaiyah Miftahul Ulum Peganden has implemented strategic management of deep education improve teacher professionalism